Secondary battery electrolyte and secondary sodium ion battery containing same
By adding the acid anhydride compound A containing silicon-based functional groups to the sodium ion battery electrolyte to form a stable interface film, the problem of electrolyte decomposition and internal resistance growth of sodium ion battery under high voltage and high nickel content is solved, and the circulation and high temperature performance of the battery are significantly improved.
Patent Information
- Application Number
- CN202311298837.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-09
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-10-09
AI Technical Summary
After the voltage and nickel content of existing sodium ion batteries increase, the positive electrode material has high surface activity, which can easily lead to oxidation and decomposition of the electrolyte, increase internal resistance, and deterioration of cycle life and high temperature performance.
An electrolyte containing a non-aqueous organic solvent, an inorganic salt and a specific additive is used, and the additive contains an acid anhydride compound A with silicon-based functional groups. The compound forms a stable SEI passivation film at the interface of the negative electrode and partially decomposes the cathode CEI film at the interface of the positive electrode to inhibit the oxidation and decomposition of the electrolyte.
By forming a stable interface film, the continuous reaction between the solvent and the negative electrode interface is inhibited, the circulation and high-temperature performance of the battery is improved, the decomposition of electrolytes is reduced, and the comprehensive performance of secondary sodium ion batteries is improved.
Smart Images

Figure BDA0004483933980000022 
Figure BDA0004483933980000031 
Figure BDA0004483933980000091
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a secondary battery electrolyte and a secondary sodium ion battery containing the electrolyte. Background Art
[0002] Secondary sodium-ion batteries have been widely used in power, energy storage, and 3C digital fields. In the field of power batteries, the pursuit of longer endurance and cycle life is mainly achieved by increasing the battery's charging voltage or increasing the nickel content of the positive electrode material to increase the battery's specific energy density. At present, layered oxides are used as positive electrode materials in both high-nickel and high-voltage ternary routes, which have good rate performance, good cycle life, and high specific energy. However, with the continuous increase in voltage and nickel content, the performance of sodium-ion batteries faces great challenges. First, after the voltage or nickel content of the layered system increases, the surface activity of the positive electrode material is higher, which easily causes the electrolyte to oxidize and decompose; secondly, the material structure changes during the use of the battery, and the positive electrode material is more likely to dissolve transition metal ions and produce oxygen release behavior, thereby further catalyzing the decomposition of the electrolyte, increasing the internal resistance of the sodium-ion battery, and significantly deteriorating the cycle life and high-temperature performance.
[0003] At present, the material system represented by layered oxides is developing rapidly and can be used as a supplement to sodium-ion batteries. Layered oxide sodium-ion batteries have many common characteristics with secondary sodium-ion batteries in terms of structural characteristics, surface characteristics, working principles, alkaline properties, etc., but they are more complicated, mainly reflected in the easy production of gas during circulation and storage, insufficient high-temperature cycle life and calendar life, rapid growth of internal resistance, and easy sodium precipitation during battery use. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the above-mentioned background technology and provide a secondary battery electrolyte and a secondary sodium ion battery containing the electrolyte. The secondary battery electrolyte of the present invention comprises a non-aqueous organic solvent, an inorganic salt and an additive, wherein the additive comprises an acid anhydride compound A containing a silicon-based functional group, and the compound A can form a stable SEI passivation film at the negative electrode interface to inhibit the continuous reaction between the solvent and the negative electrode interface; it can also partially decompose at the positive electrode interface before the solvent to form a cathode CEI film, inhibiting the oxidative decomposition of the electrolyte at the positive electrode interface, and improving the battery's cycle and high temperature performance; at the same time, the acid anhydride and silicon-based functional groups contained in the compound are used to devour and eliminate the active proton hydrogen in the battery system, which can reduce the decomposition of the electrolyte and thereby improve the comprehensive performance of the secondary sodium ion battery.
[0005] To achieve the purpose of the present invention, the secondary battery electrolyte of the present invention comprises a non-aqueous organic solvent, an inorganic salt and an additive, wherein the additive comprises an acid anhydride compound A containing a silicon-based functional group, and the structure thereof is Wherein, M is one of -CH2-CH2- or -CH2-CH-CH2-, n is an integer of 1-5, and R1, R2, and R3 are independently selected from alkyl, alkenyl, alkynyl, isocyanate, and nitrile groups with 1 to 5 carbon atoms.
[0006] Further, in some embodiments of the invention, the compound A is at least one of compounds A1-A10:
[0007]
[0008]
[0009] Furthermore, in some embodiments of the invention, the amount of compound A added is 0.05-2% of the total weight of the electrolyte.
[0010] Preferably, in some embodiments of the invention, the amount of compound A added is 0.2-2%, such as 0.2-1%, and also such as 0.2-0.5%, of the total weight of the electrolyte.
[0011] Furthermore, in some embodiments of the invention, the additives also include additives other than compound A, and the additives other than compound A are selected from two or more additives selected from vinyl sulfate, 3-tert-butyldimethylsilyloxyglutaric anhydride sulfate, vinylene carbonate, 1,3-propane sultone, 1,3-propylene sultone, 2,4-butane sultone, tris(trimethylsilyl) phosphate, tetravinylsilane, triallyl isocyanurate, tripropargyl phosphate, pentaerythritol tetraacrylate, 1,3,6-hexanetrinitrile, 3,3-ethylene disulfate, and 2,4,6-triallyloxy-1,3,5-triazine; preferably, the amount of additives other than compound A added is 0.5-5% of the total weight of the electrolyte.
[0012] Preferably, in some embodiments of the invention, the additives other than compound A are selected from other additives in the embodiments shown in Table 1 of the present invention, and the specific combination is the combination in Example 1 of Table 1.
[0013] Furthermore, in some embodiments of the invention, the non-aqueous organic solvent contains one or a mixture of two or more of propylene carbonate, ethylene carbonate, diethyl carbonate, ethyl methyl carbonate, dimethyl carbonate, fluoroethylene carbonate, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, methyl trifluoroethyl carbonate, difluoroethyl acetate, and ethyl difluoroacetate.
[0014] Preferably, in some embodiments of the present invention, the non-aqueous organic solvent is selected from the non-aqueous organic solvent combination in Example 1 shown in Table 1 of the present invention.
[0015] Preferably, in some embodiments of the invention, the amount of carbonate added to the non-aqueous organic solvent accounts for 60-85% of the total weight of the electrolyte.
[0016] Furthermore, in some embodiments of the invention, the inorganic salt is an inorganic sodium salt, and the inorganic sodium salt is selected from one or more of sodium hexafluorophosphate, sodium difluorophosphate, sodium difluorooxalatoborate, sodium difluorobisoxalatophosphate, sodium bis(fluorosulfonyl)imide, sodium bis(trifluorosulfonyl)imide, and sodium bis(oxalatoborate).
[0017] Preferably, in some embodiments of the invention, the inorganic salt is selected from the inorganic sodium salt combination in Example 1 shown in Table 1 of the present invention.
[0018] Preferably, in some embodiments of the invention, the mass percentage of the inorganic salt in the electrolyte is 10-20%.
[0019] On the other hand, the present invention also provides a secondary sodium ion battery, wherein the secondary sodium ion battery comprises the aforementioned secondary battery electrolyte.
[0020] The composite functional group contained in the compound A of the present invention has multifunctional properties. The anhydride functional group can form a stable SEI passivation film at the negative electrode interface, inhibit the continuous reaction between the solvent and the negative electrode interface, and improve the stability of the negative electrode interface; it can also partially decompose before the solvent at the positive electrode interface to form a cathode CEI film to passivate the positive electrode activity, thereby inhibiting the oxidative decomposition of the electrolyte at the positive electrode interface and improving the cycle and high temperature performance of the battery; in addition, the anhydride functional group and the silicon-based functional group can react with trace water and HF in the electrolyte to reduce the damage of HF to the positive and negative electrode materials.
[0021] In addition, the silicon-based functional groups in compound A can regulate the impedance of the additive and the degree of reaction activity on the positive and negative electrode surfaces. When R1, R2, and R3 are saturated alkanes, the impedance increase caused by the acid anhydride in compound A can be reduced. When R1, R2, and R3 are unsaturated groups, their complexation reaction at the positive electrode interface will be further increased, further enhancing the positive electrode protection effect. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. Additional aspects and advantages of the present invention will be given in part in the following description, and part will become apparent from the following description, or will be understood through the practice of the present invention. It should be understood that the following description is only used to explain the present invention and is not intended to limit the present invention.
[0023] When amount, concentration or other value or parameter is expressed as range, preferred range or a series of upper preferred value and lower preferred value limit range, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value and any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when disclosing range "1 to 5", described range should be interpreted as including range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5" etc. When numerical range is described in this article, unless otherwise stated, the range is intended to include its end value and all integers and fractions within the range.
[0024] Singular forms include plural references unless the context clearly indicates otherwise. "Optional" or "either" means that the subsequently described event or incident may or may not occur, and that the description includes instances where the event occurs and instances where it does not.
[0025] The indefinite articles "a" and "an" before the elements or components of the present invention have no limitation on the quantity requirements (i.e. the number of occurrences) of the elements or components. Therefore, "a" or "an" should be interpreted as including one or at least one, and the elements or components in the singular form also include the plural form, unless the quantity obviously refers to the singular form only.
[0026] In addition, the descriptions of the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" described below mean that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic expressions of the above terms do not necessarily refer to the same embodiment or example. Moreover, the technical features involved in the various embodiments of the present invention can be combined with each other as long as they do not conflict with each other.
[0027] For the convenience of description, some of the materials involved in the embodiments of the present invention and the comparative examples are described by abbreviations or English abbreviations: propylene carbonate (PC), propyl propionate (PP), fluoroethylene carbonate (FEC), 1,3-propane sultone (PS), 1,3-propylene sultone (PST), vinylene carbonate (VC), vinyl sulfate (DTD), tetravinylsilane (TVSI), triallyl isocyanurate (TAIC), 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (D2), sodium difluorooxalatoborate (NaODFB), sodium difluorophosphate (NaPO2F2), difluoroethyl acetate (DFEA), tris(trimethylsilyl) phosphate (TMSP).
[0028] Example 1
[0029] Preparation of electrolyte: In a glove box filled with argon (water content <10ppm, oxygen content <1ppm), propylene carbonate (PC), dimethyl carbonate (DEC), and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 30:20:50 to obtain a mixed solution, 10.0% NaPF6 and 3% sodium bis(fluorosulfonyl)imide (NaFSI) based on the total mass of the electrolyte are added to the mixed solution and stirred until they are completely dissolved, and then 0.5% vinylene carbonate (VC), 1% fluoroethylene carbonate (FEC), 1% 1,3-propane sultone (PS), and 0.5% 1,3-propylene sultone (PST) based on the total mass of the electrolyte are added, and the sodium ion battery electrolyte of Example 1 is obtained after stirring.
[0030] Example 2-31
[0031] Example 2-31 is also a specific example of electrolyte preparation. Except that the composition ratio of each component of the electrolyte is added as shown in Table 1, other parameters and preparation methods are the same as Example 1. The specific electrolyte formula is shown in Table 1.
[0032] Comparative Example 1
[0033] Preparation of electrolyte: In a glove box filled with argon (water content <10ppm, oxygen content <1ppm), propylene carbonate (PC), dimethyl carbonate (DEC), and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 30:20:50 to obtain a mixed solution, 10.0% NaPF6 and 3% sodium bis(fluorosulfonyl)imide based on the total mass of the electrolyte are added to the mixed solution, and the mixture is stirred until it is completely dissolved, and then 0.5% vinylene carbonate (VC), 1% fluoroethylene carbonate (FEC), and 2% 1,3-propane sultone based on the total mass of the electrolyte are added, and the sodium ion battery electrolyte of Comparative Example 1 is obtained after stirring.
[0034] Comparative Example 2
[0035] Preparation of electrolyte: In a glove box filled with argon (water content <10ppm, oxygen content <1ppm), propylene carbonate (PC), dimethyl carbonate (DEC), and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 30:20:50 to obtain a mixed solution, 10.0% NaPF6 and 3% sodium bis(fluorosulfonyl)imide based on the total mass of the electrolyte are added to the mixed solution, and the mixture is stirred until it is completely dissolved, and then 0.5% vinylene carbonate (VC), 1% fluoroethylene carbonate (FEC), and 1% 1,3-propylene sultone based on the total mass of the electrolyte are added, and the sodium ion battery electrolyte of Comparative Example 2 is obtained after stirring.
[0036] Comparative Example 3
[0037] Preparation of electrolyte: In a glove box filled with argon (water content <10ppm, oxygen content <1ppm), propylene carbonate (PC), dimethyl carbonate (DEC), and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 30:20:50 to obtain a mixed solution, 10.0% NaPF6 and 3% sodium bis(fluorosulfonyl)imide based on the total mass of the electrolyte are added to the mixed solution, and stirred until they are completely dissolved, and then 0.5% vinylene carbonate (VC), 1% fluoroethylene carbonate (FEC), 1% 1,3-propane sultone (PS), and 0.5% 1,3-propylene sultone (PST) based on the total mass of the electrolyte are added, and the sodium ion battery electrolyte of Comparative Example 3 is obtained after stirring.
[0038] Comparative Example 4
[0039] Preparation of electrolyte: In a glove box filled with argon (water content <10ppm, oxygen content <1ppm), propylene carbonate (PC), dimethyl carbonate (DEC), and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 30:20:50 to obtain a mixed solution, and 10.0% NaPF6, 3% sodium bisfluorosulfonyl imide (NaFSI), and 0.5% sodium difluorooxalatoborate (NaDFOB) based on the total mass of the electrolyte are added to the mixed solution and stirred until they are completely dissolved, and then 0.5% vinylene carbonate (VC), 1% fluoroethylene carbonate (FEC), 1% 1,3-propane sultone (PS), and 0.5% 1,3-propylene sultone (PST) based on the total mass of the electrolyte are added, and the sodium ion battery electrolyte of Comparative Example 4 is obtained after stirring.
[0040] Comparative Example 5
[0041] Preparation of the electrolyte: In a glove box filled with argon (water content <10ppm, oxygen content <1ppm), propylene carbonate (PC), dimethyl carbonate (DEC), and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 30:20:50 to obtain a mixed solution, and 10.0% NaPF6, 3% sodium bisfluorosulfonyl imide (NaFSI), and 0.5% sodium difluorooxalatoborate (NaDFOB) based on the total mass of the electrolyte are added to the mixed solution and stirred until they are completely dissolved, and then 0.5% vinylene carbonate (VC), 1% fluoroethylene carbonate (FEC), 1% 1,3-propane sultone (PS), 0.5% 1,3-propylene sultone (PST), and 1% vinyl sulfate (DTD) are added based on the total mass of the electrolyte, and the sodium ion battery electrolyte of Comparative Example 5 is obtained after stirring.
[0042] Comparative Example 6
[0043] Preparation of electrolyte: In a glove box filled with argon (water content <10ppm, oxygen content <1ppm), propylene carbonate (PC), dimethyl carbonate (DEC), and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 30:20:50 to obtain a mixed solution, and 10.0% NaPF6, 3% sodium bisfluorosulfonyl imide (NaFSI), 0.5% sodium difluorooxalatoborate (NaDFOB), and 0.5% sodium difluorophosphate (NaPO2F2) based on the total mass of the electrolyte are added to the mixed solution and stirred until they are completely dissolved, and then 0.5% vinylene carbonate (VC), 1% fluoroethylene carbonate (FEC), 1% 1,3-propane sultone (PS), and 1% vinyl sulfate (DTD) are added based on the total mass of the electrolyte, and the sodium ion battery electrolyte of Comparative Example 6 is obtained after stirring.
[0044] Comparative Example 7
[0045] Preparation of electrolyte: In a glove box filled with argon (water content <10ppm, oxygen content <1ppm), propylene carbonate (PC), dimethyl carbonate (DEC), and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 30:20:50 to obtain a mixed solution, and 10.0% NaPF6, 3% sodium bisfluorosulfonyl imide (NaFSI), 0.5% sodium difluorooxalatoborate (NaDFOB), and sodium difluorophosphate (NaPO2F2) based on the total mass of the electrolyte are added to the mixed solution and stirred until they are completely dissolved, and then 0.5% vinylene carbonate (VC), 1% fluoroethylene carbonate (FEC), 1% 1,3-propane sultone (PS), 0.5% 1,3-propylene sultone (PST), and 1% vinyl sulfate (DTD) are added based on the total mass of the electrolyte, and the sodium ion battery electrolyte of Comparative Example 7 is obtained after stirring.
[0046] Table 1 Electrolyte compositions of Comparative Examples 1-7 and Examples 1-31
[0047]
[0048]
[0049] Effect Example
[0050] Using improved O3-type layered oxide NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 positive electrode material, hard carbon as negative electrode material, aluminum foil as positive and negative electrode current collector, and polypropylene film as separator are prepared into soft-pack batteries. Then, the electrolytes of the above-mentioned Examples 1-31 and Comparative Examples 1-7 are injected, and the sodium ion soft-pack batteries to be tested are obtained through packaging, storage, formation, aging, sodium ion packaging, and capacity separation.
[0051] 1. Normal temperature cycle performance
[0052] Under normal temperature (25±2℃), the sodium ion battery is charged to 4.0V at 1C constant current and constant voltage, with a cut-off current of 0.05C; left for 5 minutes, then discharged to 2.0V at constant current, left for 5 minutes, and the charge and discharge cycle is repeated. The average capacity of the battery in the first three weeks is the initial capacity A1, and the capacity after the nth cycle is An. The capacity retention rate for the nth cycle can be calculated by (An / A1)*100%.
[0053] 2. High temperature cycle performance
[0054] Under high temperature (45±2℃), the sodium ion battery is charged to 4.0V at 1C constant current and constant voltage, with a cut-off current of 0.05C; left for 5min, then discharged to 2.0V at constant current, left for 5min, and the charge and discharge cycle is repeated. The average capacity of the battery in the first three weeks is the initial capacity C1, and the capacity after the nth cycle is Cn, which can be calculated by (C 600 / C1)*100% to obtain the 600th capacity retention rate.
[0055] 3. Low temperature -20℃ performance
[0056] At room temperature (25±2℃), the sodium ion battery is charged to 4.0V at 1C constant current and constant voltage, with a cut-off current of 0.05C; left for 5 minutes, and then discharged to 2.0V at 1C constant current, and the discharge capacity is recorded as B1. The battery is charged to 4.0V at 1C constant current and constant voltage again, with a cut-off current of 0.05C; then the battery is placed in a low temperature environment of -20℃, left for 4 hours, and then discharged to 1.5V at 1C constant current, and the discharge capacity is recorded as B2. The 1C discharge ratio at low temperature of -20℃ can be calculated by (B2 / B1)*100%.
[0057] 4. High temperature storage performance
[0058] Under high temperature (60±2°C), the sodium ion battery was charged and discharged at 1C / 1C (the discharge capacity was recorded as DC0), the initial thickness was recorded as D1, the initial internal resistance was R1, and then the sodium ion soft pack battery was charged to 4.0V under 1C constant current and constant voltage conditions; the fully charged sodium ion battery was placed in a 60°C high temperature box for 7 days, and the thickness was measured as D2 immediately after it was taken out, and 1C discharge was performed at room temperature (the discharge capacity was recorded as DC1); the internal resistance was tested with an AC internal resistance meter as R2, and then 1C / 1C charging and discharging was performed at room temperature (the discharge capacity was recorded as DC2), and the thickness change rate, internal resistance change rate, DCR change rate, capacity retention rate and capacity recovery rate of the sodium ion battery were calculated using the following formulas:
[0059]
[0060]
[0061]
[0062]
[0063] Table 2 Battery performance test results of Comparative Examples 1-7 and Examples 1-31
[0064]
[0065]
[0066] According to the room temperature cycle, high temperature 45°C cycle, low temperature -20°C discharge performance, and 60°C storage performance of Comparative Examples 1-7 and Examples 1-31 in Table 2 above, it can be seen that in the electrolyte solution with sodium hexafluorophosphate and sodium bis(fluorosulfonyl)imide as mixed salts and PC / DEC / EMC=3 / 2 / 5 solvent system, negative electrode film-forming additives VC and FEC and high temperature additive PS are added to the electrolyte. The high and low temperature performance and cycle performance are poor, the battery high temperature storage thickness increases a lot, and the capacity retention rate is low. Disassembling the battery found that the group of batteries had sodium precipitation during the cycle, indicating that there is a large negative effect of enhancing the high temperature performance of the battery by increasing PS. After PST was used to replace PS in Comparative Example 2, the comprehensive performance was improved compared with the comprehensive performance of the battery in Comparative Example 1. In Comparative Example 3, after using PS and PST as high temperature additives, the cycle performance was further improved. Excessive content of PST and PS is not conducive to the low temperature and cycle performance of sodium electricity, and there is a risk of sodium precipitation. By further adding low-impedance materials such as vinyl sulfate (Comparative Example 5), sodium difluorooxalatoborate and sodium difluorophosphate (Comparative Example 6 / 7) into the sodium battery electrolyte, the room temperature cycle life of the sodium battery is significantly improved, and the high temperature performance is enhanced. The low temperature discharge ratio is increased from 70% to more than 80%, indicating that inorganic salt additives have a good ability to improve the cycle and high and low temperature performance in layered sodium batteries.
[0067] Example 1 is based on Comparative Example 3. 0.5% of A1 is added to the additive. The cycle life at room temperature and high temperature is improved, the low-temperature discharge performance is close, and the high-temperature storage capacity retention rate and recovery rate are improved. By adding 0.5% of sodium difluorooxalate borate and 0.5% of sodium difluorophosphate to the electrolyte based on Example 1, the comprehensive performance of the sodium ion battery is further enhanced, and the low-temperature performance is also significantly improved. Due to the presence of anhydride functional groups in compound A, it can form a film at the negative electrode before the solvent, and at the same time decompose on the surface of the positive electrode, increase the positive electrode interface impedance, and thus reduce the low-temperature performance. Through the composite use of new inorganic salts, the proportion of inorganic SEI film at the positive and negative electrode interfaces can be adjusted, the internal resistance of sodium ion charge transfer can be reduced, and the transmission performance of sodium ions can be improved. By comparing the battery data of the addition amount of compound A1 (Examples 3-7), it can be found that when the addition amount of compound A1 is 0.1%, the improvement of its comprehensive performance relative to the benchmark group is limited, indicating that when the addition amount of compound A1 is too small, a dense interface film cannot be formed at the interface. When the addition amount of compound A1 is increased to 1-2%, the high-temperature energy storage performance of sodium electricity has decreased. This may be due to the fact that the additive remains in the battery system after formation, and the residual part is unstable at high temperature and decomposes and consumes, resulting in a decrease in high-temperature performance. At the same time, the excessive introduction of the compound will further increase the interface impedance, degrade the room temperature cycle performance and low-temperature discharge capacity, and increase the risk of sodium electrolysis. By comparing the performance of compounds A (Examples 9-17) with different structures, it is found that the comprehensive performance of compound A is better than 1,3-propylene sultone. When the silicon-based functional group substituent in compound A is a saturated alkane (methyl, ethyl), the room temperature performance is better than that of the additive with an unsaturated group in the silicon-based functional group, and the high temperature performance is slightly inferior to that of the additive containing an unsaturated bond. When R1, R2, and R3 in compound A are saturated alkanes, the impedance increase caused by the presence of anhydride in compound A can be reduced. When R1, R2, and R3 are unsaturated groups, the complexation reaction at the positive electrode interface will be further increased, further enhancing the positive electrode protection effect.
[0068] Furthermore, the overall performance of sodium batteries can be further improved by optimizing the solvent system. After introducing some carboxylate PP into the solvent system of the electrolyte, the high-temperature gas production is reduced, and the cycle life at room temperature and high temperature is enhanced. Studies have found that carboxylate PP can react rapidly with trace amounts of Na metal precipitated in the sodium battery system, inhibiting the precipitation of sodium dendrites, thereby reducing the continuous reduction of metallic sodium and solvents. The room-temperature cycle performance and low-temperature discharge capacity of fluoroethers and fluorocarboxylates in the battery system are further improved, showing the performance advantages of fluorinated solvents in the sodium battery system. Studies have found that fluorinated compounds can increase the sodium fluoride interface film component in the sodium battery system, reduce the impedance of the battery, and enhance the stability of the interface. At the same time, fluorinated solvents also have an inhibitory effect on the precipitation of sodium metal. Controlling the precipitation of sodium metal in the sodium battery system has become the key to improving the performance of sodium batteries.
[0069] In summary, by introducing compound A into the sodium electrolyte of layered oxide, the high temperature and high temperature cycle life of layered sodium ion batteries can be significantly improved, the storage performance of sodium ion batteries can be enhanced, and the cycle stability and high and low temperature performance of sodium batteries can be further improved by the composite modification of new inorganic sodium salts and sodium hexafluorophosphate. The introduction of carboxylic acid esters and fluorinated solvents reduces the risk of sodium precipitation in layered sodium ion batteries, improves the interface kinetics, and thus improves the comprehensive performance of sodium ion batteries. The composite functional groups contained in the above compound A have multifunctional properties. The anhydride functional group can form a stable SEI passivation film at the negative electrode interface, inhibit the continuous reaction between the solvent and the negative electrode interface, and improve the stability of the negative electrode interface; it can also partially decompose at the positive electrode interface before the solvent to form a cathode CEI film to passivate the positive electrode activity, thereby inhibiting the oxidative decomposition of the electrolyte at the positive electrode interface and improving the battery's cycle and high temperature performance. In addition, the anhydride functional group and the silicon-based functional group can react with trace water and HF in the electrolyte, which can reduce the damage of HF to the positive and negative electrode materials. The silicon-based functional groups in compound A can regulate the impedance of the additive and the degree of reaction activity on the positive and negative electrode surfaces. When R1, R2, and R3 are saturated alkanes, the impedance increase caused by the acid anhydride in compound A can be reduced. When R1, R2, and R3 are unsaturated groups, the complexation reaction at the positive electrode interface will be further increased, further enhancing the positive electrode protection effect.
[0070] Those skilled in the art will easily understand that the above descriptions are merely embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A secondary battery electrolyte, characterized in that: The secondary battery electrolyte contains a non-aqueous organic solvent, an inorganic salt and an additive, wherein the additive contains an acid anhydride compound A containing a silicon-based functional group, and the structure thereof is Wherein, M is one of -CH2-CH2- or -CH2-CH-CH2-, n is an integer of 1-5, and R1, R2, and R3 are independently selected from alkyl, alkenyl, alkynyl, isocyanate, and nitrile groups with 1 to 5 carbon atoms.
2. The secondary battery electrolyte according to claim 1, characterized in that: The compound A is at least one of compounds A1-A10:
3. The secondary battery electrolyte according to claim 1, characterized in that: The added amount of the compound A accounts for 0.05-2% of the total weight of the electrolyte.
4. The secondary battery electrolyte according to claim 1, characterized in that: The amount of compound A added is 0.2-2% of the total weight of the electrolyte, such as 0.2-1%, and also 0.2-0.5%.
5. The secondary battery electrolyte according to claim 1, characterized in that: The additives further include additives other than compound A, and the additives other than compound A are selected from two or more additives selected from vinyl sulfate, 3-tert-butyldimethylsilyloxyglutaric anhydride propylene sulfate, vinylene carbonate, 1,3-propane sultone, 1,3-propylene sultone, 2,4-butane sultone, tris(trimethylsilyl) phosphate, tetravinylsilane, triallyl isocyanurate, tripropargyl phosphate, pentaerythritol tetraacrylate, 1,3,6-hexanetrinitrile, 3,3-ethylene disulfate, and 2,4,6-triallyloxy-1,3,5-triazine; preferably, the additive amount of the additives other than compound A accounts for 0.5-5% of the total weight of the electrolyte.
6. The secondary battery electrolyte according to claim 1, characterized in that: The non-aqueous organic solvent contains one or a mixture of two or more of propylene carbonate, ethylene carbonate, diethyl carbonate, ethyl methyl carbonate, dimethyl carbonate, fluoroethylene carbonate, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, methyl trifluoroethyl carbonate, difluoroethyl acetate, and ethyl difluoroacetate.
7. The secondary battery electrolyte according to claim 6, characterized in that: The addition amount of carbonate in the non-aqueous organic solvent accounts for 60-85% of the total weight of the electrolyte.
8. The secondary battery electrolyte according to claim 1, characterized in that: The inorganic salt is an inorganic sodium salt, and the inorganic sodium salt is selected from one or more of sodium hexafluorophosphate, sodium difluorophosphate, sodium difluorooxalatoborate, sodium difluorobisoxalatophosphate, sodium bisfluorosulfonyl imide, sodium bistrifluorosulfonyl imide, and sodium bisoxalatoborate.
9. The secondary battery electrolyte according to claim 1, characterized in that: The mass percentage of the inorganic salt in the electrolyte is 10-20%.
10. A secondary sodium ion battery, characterized in that: The secondary sodium ion battery comprises the secondary battery electrolyte according to any one of claims 1 to 9.
Citation Information
Patent Citations
Lithium ion battery non-aqueous electrolyte and application thereof
CN113839093A
Sodium-ion battery electrolyte and sodium-ion battery
CN119153776A
Carrier and process for producing it
JP2009229320A
Non-aqueous electrolyte solution for lithium secondary battery and lithium secondary battery comprising the same
US20170162905A1
Anode material and lithium ion battery applying same
WO2016173469A1
Cited By
Electrolyte and sodium ion battery
WO2026148764A1